1974
DOI: 10.1038/icb.1974.8
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐initiated B Lymphocyte Differentiation. Characterisation of the Primary and Secondary Immune Responses of Normal and Athymic Mice to the Hapten 4‐hydroxy‐3‐iodo‐5‐nitrophenylacetic Acid Presented on the Carrier Polymerised Bacterial Flagellin

Abstract: Summary The hapten 4‐hydroxy‐3‐iodo‐5‐nitrophenylacetic acid (NIP) has been coupled to polymerised bacterial flagellin (POL) to produce a linear array of repetitive antigenic determinants. The kinetics and nature of the immune response to this antigen have been studied in normal and athymic nude mice. The primary immune response by normal mice involved exclusively IgM antibody‐forming cells (AFC), whereas the response by normal mice primed to the NIP determinant consisted of IgG as well as IgM AFC. Both the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…CBA (H-2k) mice were immunized with 4-hydroxy-3-iodo-5-nitrophenyl acetic acid conjugated to polymerized flagellin (NIP-POL) as previously described (Schlegel, 1974). After 3 or 7 days, mice were killed, their spleens removed and assayed for haemolytic plaque forming cells.…”
Section: A Antigens On Plaque Forming Cellsmentioning
confidence: 99%
“…CBA (H-2k) mice were immunized with 4-hydroxy-3-iodo-5-nitrophenyl acetic acid conjugated to polymerized flagellin (NIP-POL) as previously described (Schlegel, 1974). After 3 or 7 days, mice were killed, their spleens removed and assayed for haemolytic plaque forming cells.…”
Section: A Antigens On Plaque Forming Cellsmentioning
confidence: 99%
“…Both techniques were needed to give an estimate of cell size (14). These methods were used in conjunction with an adoptive immune assay of IgM AFC progenitors reactive to the hapten 4hydroxy-3-iodo-5-nitrophenylacetic acid (NIP) conjugated to the carrier polymerized bacterial flagellin (POL) (11,(15)(16)(17). Previous studies have indicated that the CBA mouse is in a relatively unprimed state with respect to this hapten (11,15,16).…”
mentioning
confidence: 99%
“…These methods were used in conjunction with an adoptive immune assay of IgM AFC progenitors reactive to the hapten 4hydroxy-3-iodo-5-nitrophenylacetic acid (NIP) conjugated to the carrier polymerized bacterial flagellin (POL) (11,(15)(16)(17). Previous studies have indicated that the CBA mouse is in a relatively unprimed state with respect to this hapten (11,15,16). The assay allows a direct measurement of AFC progenitor function, under conditions where AFC production bears a direct, linear, arithmetic relationship to the number of progenitors transferred (17).…”
mentioning
confidence: 99%
“…The splenic AFC response of CBA mice to an antigen such as NIP-POL (nitroiodo phenol hapten and polymerised bacterial flagellin carrier) char-13" 196 NOSSAL ET AL. , acteristicaily shows two i>eaks, around day 3-4 and day 8 (Schlegel 1974), as shown in Figure 1. This recalls the cycling AFC production kinetics reported in several systems (reviewed by Weigle 1975), but we believe in this case the two peaks derive not from oscillating feedback effects, but from two separate, sequentially related progenitor populations.…”
Section: Experimental Evidence For the Pre-progenitor -Direct Afc Promentioning
confidence: 89%